Long Non-coding RNA MALAT1 Is Depleted With Age in Skeletal Muscle in vivo and MALAT1 Silencing Increases Expression of TGF-β1 in vitro - Ruan, Ling; Mendhe, Bharati; Parker, Emily; Kent, Andrew; Isales, Carlos M.; Hill, William D.; McGee-Lawrence, Meghan; Fulzele, Sadanand; Hamrick, Mark W. (Frontiers in Physiology, 2022)
Long non-coding RNAs (lncRNAs) are thought to function as “sponges” for microRNAs, but a role for such competing endogenous RNAs (ceRNA) in muscle aging is not well understood. We therefore examined in skeletal muscles of young (4-6 mos) and aged (22-24) male and female mice the expression of lncRNA MALAT1, which is predicted in silico to bind the senescence-associated microRNA miR-34a-5p. Results indicate a significant decrease in lncRNA MALAT1 expression in mouse skeletal muscle with age that coincides with an age-related increase in miR-34a-5p expression. In vitro studies using mouse C2C12 myoblasts demonstrate that MALAT1 silencing using siRNA increases miR-34a expression, consistent with a role for MALAT1 as an inhibitor of miR-34a-5p activity. Levels of reactive oxygen species (ROS) are known to increase in muscle with age, and so we treated C2C12 cells with hydrogen peroxide (10, 100 µM) to examine changes in MALAT1 expression. MALAT1 expression decreased significantly with H2O2 treatment, but this effect was attenuated with p53 siRNA. Finally, miR-34a-5p is implicated in tissue fibrosis, and so we assessed the expression of TGF-β1 after MALAT1 silencing. MALAT1 siRNA significantly increased the expression of TGF-β1 in C2C12 cells. These findings suggest that age-related fibrosis and muscle atrophy mediated by ROS may result at least in part from an increase in miR-34a bioavailability resulting from a decline in miR-34a “sponging” due to ceRNA MALAT1 depletion. Crosstalk between MALAT1 and miR-34a may therefore represent a therapeutic target for improving muscle function with aging.